CyberKnife MLC-based treatment planning for abdominal and pelvic SBRT: Analysis of multiple dosimetric parameters, overall scoring index and clinical scoring. (December 2018) - Masi, Laura; Zani, Margherita; Doro, Raffaela; Calusi, Silvia; Di Cataldo, Vanessa; Bonucci, Ivano; Cipressi, Samantha; Francolini, Giulio; Bonomo, Pierluigi; Livi, Lorenzo
Highlights: Comparing Iris and MLC plan quality for 56 CyberKnife abdominal and prostate SBRT cases. Comparison based on a overall mathematical scoring index and on clinical scoring. Iris and MLC comparison was not straightforward when based on multiple parameters. Mathematical and clinical scoring proved essential to evaluate MLC plans advantages. Time reduction achievable by MLC is highly variable among different published studies. Abstract: Purpose: This study evaluated the plan quality of CyberKnife MLC-based treatment planning in comparison to the Iris collimator for abdominal and pelvic SBRT. Multiple dosimetric parameters were considered together with a global scoring index validated by clinical scoring. Methods and materials: Iris and MLC plans were created for 28 liver, 15 pancreas and 13 prostate cases including a wide range of PTV sizes (24–643 cm 3 ). Plans were compared in terms of coverage, conformity (nCI), dose gradient (R50%), homogeneity (HI), OAR doses, PTV gEUD, MU, treatment time both estimated by TPS (tTPS ) and measured. A global plan quality score index was calculated for IRIS and MLC solutions and validated by a clinical score given independently by two observers. Results: Compared to Iris, MLC achieved equivalent coverage and conformity without compromising OAR sparing and improving R50% (p < 0.001). MLC gEUD was slightly lower than Iris (p < 0.05) for abdominal cases. MLC reduced significantly MU (−15%) and tTPS (−22%). Time reduction was partially lost when measured. The global score index was significantly higher for MLC solutions which were selected in 73% and 64% of cases respectively by the first and second observer. Conclusion: Iris and MLC comparison was not straightforward when based on multiple dosimetric parameters. The use of a mathematical overall score index integrated with a clinical scoring was essential to confirm MLC plans advantages over Iris solutions.